Evolution of fluoroquinolone-resistant Escherichia coli in the gut after ciprofloxacin treatment - de Lastours, V.; El Meouche, I.; Chau, F.; Beghain, J.; Chevret, D.; Aubert-Frambourg, A.; Clermont, O.; Royer, G.; Bouvet, O.; Denamur, E.; Fantin, B. (International journal of medical microbiology, 2022)
Three healthy volunteers carried similar quinolone-resistant E. coli (QREC) (pulsed field gel electrophoresis profiles) in their gut before and after 14 days ciprofloxacin treatment. Given the intensity of the selective pressure and the mutagenic properties of quinolones, we determined whether these strains had evolved at the phenotypic and/or genomic levels. Commensal QREC from before day-0 (D0), and a month after 14 days of ciprofloxacin (D42) were compared in 3 volunteers. Growth experiments were performed; acetate levels, mutation frequencies, quinolone MICs and antibiotic tolerance were measured at D0 and D42. Genomes were sequenced and single nucleotide polymorphisms (SNPs) between D0 and D42 were analyzed using DiscoSNP and breseq methods. Cytoplasmic proteins were extracted, HPLC performed and proteins identified using X!tandem software; abundances were measured by mass spectrometry using the Spectral Counting (SC) and eXtraction Ion Chromatograms (XIC) integration methods. No difference was found in MICs, growth characteristics, acetate concentrations, mutation frequencies, tolerance profiles, phylogroups, O-and H-types, fimH alleles and sequence types between D0 and D42. No SNP variation was evidenced between D0 and D42 isolates for 2/3 subjects; 2 SNP variations were evidenced in one. At the protein level, very few significant protein abundance differences were identified between D0 and D42. No fitness, tolerance, metabolic or genomic evolution of commensal QREC was observed overtime, despite massive exposure to ciprofloxacin in the gut. The three strains behaved as if they had been unaffected by ciprofloxacin, suggesting that gut may act as a sanctuary where bacteria would be protected from the effect of antibiotics and survive without any detrimental effect of stress.